KAUM SANTRI MOJOKUTO DAN KAUM SANTRI FRONT PEMBELA ISLAM (Studi Tentang Oposisi Biner: Kolot dan Modernis dalam Konsepsi Cliffor Geertz) - . Mustari (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
Research on the influence of Arabic syntax to Malay language orIndonesia language in 19th century is really difficult to be found. In fact, the 19th century is the century that is important in the assessment phase of the Indonesia grammar (Malay), because in this phase began many grammar books and dictionaries of Malay language, both written by Europeans (British-Dutch- French), as Marsden (1812), Crawfurd (1852), Favre (1875), Hollander (1882), and Wijk (1889), as well as written by the Malay people Raja Ali Haji (1850 and 1859).There are fundamental differences between the grammar books written by the Dutch and the Malays. Books written by Europeans was Europe-centric, while the book written by the Malays are very Arab-centric. In fact, since Islam arrived in the archipelago, the influences of Arabic syntax are felt in the archipelago texts, especially religious texts. The fact that the Arabic influence is strong enough to precisely the Malay language syntax encourage Ronkel (1899) wrote an article entitled "Over Invloed der Arabische Syntaxis op de Maleische". Bustān al- Kātibīn is the first book written by country boy, who was very clearly demonstrated the influence of Malay language to Arabic language. The influence was not only in vocabulary, but also on the structure and rule of grammar.Keywords: Syntax, Arabic language, Malay language